2013
DOI: 10.1158/0008-5472.can-12-1752
|View full text |Cite
|
Sign up to set email alerts
|

The Planar Cell Polarity Pathway Drives Pathogenesis of Chronic Lymphocytic Leukemia by the Regulation of B-Lymphocyte Migration

Abstract: The planar cell polarity (PCP) pathway is a conserved pathway that regulates cell migration and polarity in various contexts. Here we show that key PCP pathway components such as Vangl2, Celsr1, Prickle1, FZD3, FZD7, Dvl2, Dvl3, and casein kinase 1 (CK1)-ε are upregulated in B lymphocytes of patients with chronic lymphocytic leukemia (CLL). Elevated levels of PCP proteins accumulate in advanced stages of the disease. Here, we show that PCP pathway is required for the migration and transendothelial invasion of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
99
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 43 publications
6
99
0
Order By: Relevance
“…As noted in this and prior studies, 4,16,17 Wnt5a could enhance leukemiacell migration, proliferation, and survival of ROR1…”
Section: Discussionsupporting
confidence: 77%
“…As noted in this and prior studies, 4,16,17 Wnt5a could enhance leukemiacell migration, proliferation, and survival of ROR1…”
Section: Discussionsupporting
confidence: 77%
“…Overexpression of the PCP protein leads to increased cell survival and cell migration of leukemic cells and confers a poor prognosis to patients independently of other risk factors (27). Similar conclusions were recently drawn from studies done in chronic lymphocytic leukemia in which a set of PCP proteins is upregulated (30).…”
supporting
confidence: 64%
“…Kaucká et al 33 recently reported that the planar cell polarity pathway, a noncanonical Wnt pathway, drives CLL pathogenesis by regulating B-lymphocyte migration. 29 Other investigators have shown LEF1 to inhibit CYLD, which leads to dysregulation of tumor necrosis factor-induced necroptotic signaling, thereby providing a link between survival of CLL cells and active Wnt signaling. At the same time, a large-scale genomewide association study identified multiple risk loci for CLL that included BCL2, LEF1, and other genes, 1 again highlighting the role of Wnt pathway dysregulation as a genetic factor associated with susceptibility for CLL.…”
Section: Discussionmentioning
confidence: 99%
“…CSNK1E is a member of the noncanonical Wnt pathway, which was recently characterized to play a significant role in B-lymphocyte migration in CLL. 29 Hence, mutation in this gene may have only observable effects within a B-cell context. As for the other 4 Wnt pathway mutations with no effects on CLL survival after knockdown, the absence of the signal could be attributed to the idea that these are bona fide "passenger mutations," or that they have effects on other pathways that affect CLL, but were not measureable solely based on the cell viability readout on which we focused.…”
Section: Discussionmentioning
confidence: 99%